2019
DOI: 10.1596/1813-9450-8882
|View full text |Cite
|
Sign up to set email alerts
|

Employment Data in Household Surveys: Taking Stock, Looking Ahead

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…We make use of both self-reported answers and those reported by proxy. For our sample, 44 per cent of the data on economic activity were proxy-reported, which is fairly standard in household survey data internationally, and compares favourably to the levels of proxy reporting in other household surveys, such as the United States' Current Population Survey (Boehm 1989;Desiere and Costa 2019). As noted above, our analysis is limited to the sample of workers to whom South Africa's labour law pertains most extensively -those workers covered by an SD.…”
Section: Descriptive Data: Estimates Of Non-compliancementioning
confidence: 90%
“…We make use of both self-reported answers and those reported by proxy. For our sample, 44 per cent of the data on economic activity were proxy-reported, which is fairly standard in household survey data internationally, and compares favourably to the levels of proxy reporting in other household surveys, such as the United States' Current Population Survey (Boehm 1989;Desiere and Costa 2019). As noted above, our analysis is limited to the sample of workers to whom South Africa's labour law pertains most extensively -those workers covered by an SD.…”
Section: Descriptive Data: Estimates Of Non-compliancementioning
confidence: 90%
“…There are a few studies that deal with the issues of reliability and differences between self and proxy reporting in developing countries (Fisher et al 2010;Bardasi et al 2010;Dillon et al 2012;Dammert and Galdo 2013;Desiere and Costa 2019;Koolwal 2019;Kilic et al 2020). A major study which provides an analysis of differences in self and proxy reporting for adult labor outcomes in developing countries is Bardasi et al (2010).…”
Section: Empirical Studies Of Self Vs Proxy Reporting Differencesmentioning
confidence: 99%
“…Overall, most of the evidence on the differences, quality, and reliability of self/proxy reporting comes from the U.S. (Bardasi et al 2010). There are several studies known to the authors which provide an analysis of differences in self and proxy reporting for adult labor outcomes in developing countries (Bardasi et al 2010;Desiere and Costa 2019;Koolwal 2019;Kilic et al 2020). However, neither of these studies examines the causes of differences in reporting and potential deliberate misreporting by respondents.…”
Section: Introductionmentioning
confidence: 99%
“…The survey did not record the time spent on each individual, only the time spent on the entire module. 11 The review by Desiere and Costa (2019) of the labor module data of LSMS surveys across six countries in Africa indicates that the rate of self-report responses ranged from 15% in Mali to 76% in Nigeria. in order to avoid additional associated follow-up questions.…”
Section: Data and Empirical Strategymentioning
confidence: 99%
“…6 Some papers have shown that design choices and features can induce biases in resulting data, consistent with the findings in this paper. For example, Galdo et al (2020), Desiere and Costa (2019), and Comblon et al (2015) show how question phrasing and recall windows can induce biases by age and gender in survey responses.…”
Section: Introductionmentioning
confidence: 99%